Population survey of Holothuria (Halodeima) grisea (Aspidochirotida: Holothuriidae) at its limit of geographic distribution in the Western South Atlantic - Sabino Rupp, Guilherme (2024)
Introduction: The sea cucumber Holothuria (Halodeima) grisea Selenka, 1867 is a common echinoderm in intertidal regions along the Brazilian coast, which recently became the focus of unreported and unregulated fisheries. This study was carried out in sandy-rocky substrates at Armação do Itapocoroy, Penha, Santa Catarina (26o47’ S; 48o36’ W), near its southern limit of geographic distribution. Objective: To determine the densities (individuals*m-2) of Holothuria (H.) grisea within a spatial-temporal perspective as well as to determine biometric and growth characteristics of the population. Methods: Two-meter wide transects perpendicular to the coastline were carried out in winter and spring 2019 and in summer and spring 2020, in periods of spring low-tides. In each sampling occasion the total number of specimens of H. grisea were determined, and a group of 90 organisms was submitted to in situ biometrics (weight, length and width), and immediately returned alive to their habitat. Results: The densities of H. (H.) grisea were significantly higher in the subtidal sector and lower in the upper intertidal sector with no indication of significant differences among sampling campaigns. Depth was the primary factor explaining the observed density patterns and rugosity of the substrate was secondary but also important. The body length ranged from 5.2 to 22.5 cm, whereas the weight varied from 6.0 to 230 g. The mean and modal lengths were 12.54 and 13 cm, respectively. Approximately 75 % of the population sampled was between 10 and 14 cm and the average weight was 60 g. Estimates from von Bertalanffy growth function indicate that the youngest sea cucumber was one year-old, and the oldest had approximately two and a half years. Conclusions: This is the first study to determine biometric parameters for H. (H.) grisea in southern Brazil and the first one to estimate growth and age estimates for a wild population of this species. The densities recorded in the present study were lower than those previously reported for this region, suggesting anthropic influence.